The rise and fall of the privatized pension system in Chile : an international perspective - Solimano, Andrés (London : Anthem Press, 2021)
'The Rise and Fall of the Privatized Pension System in Chile' focuses on the Chilean experience with a privatised pension system since the early 1980 when launched by the Pinochet regime. It explores economic, financial and political economy dimensions of a private pension system based on individual savings capacity implemented in a highly unequal country. The book also highlights the role played by the pension system as a mechanism of savings redistribution from wage earners and the self-employed to the funding of big corporations at home and abroad, in a process intermediated by profit-making pension fund management companies. The book compares the resilience of Chile's private pension system with the reversals of the privatised pension system in recent years in countries of Latin America and Central-Eastern Europe. It outlines a program of structural pension reform towards a more progressive, public-based system.
Title from publisher's bibliographic system (viewed on 26 Mar 2021).
Keywords: Pensions -- Chile -- History -- 20th century; Pensions -- Chile -- History -- 21st century; Privatization -- Chile